Architectural interventions in the Palace of the Admiral of Aragón in Valencia (early 20th century) - Antonio Gómez Gil (Virtual Archaeology Review)
The Palace of the Admirals of Aragón is in the city of Valencia, Spain. It was built in the Gothic style of the Valencian self-governing period, and has always been an “architectonic type” reference of this era. Referring to the building itself, there are two elements to highlight because of their interest. The first is its courtyard, which fits into the developed standards in all states of the old Crown of Aragón, talking about either the ones currently in Spain or those existing in France or Italy. Because of that, researchers came up with the term “Mediterranean Gothic” to define this style, since there are currently different geographic regions belonging to different countries. This courtyard will be the main research objective of this paper; it was designed before the ground floor, first floor and small attic interventions. The second element which makes this building unique is its ceilings of carved painted woodwork. Until the present day, this Palace has only been refurbishment once (in 1987), according to written records. The aim of this paper is to show that even though the courtyard has always been used as the best way to show the Valencian Gothic style, many of its elements were added in the first half of the 20th Century. In this research, it can be deduced that there were at least three technicians in the period between 1902 and the late 30s. Surveyor Salvador Furió, who simply put some order into interior partitions where a Gothic spiral staircase was demolished, carried out the first intervention. In the late 1920s, the work was taken over by architect Joaquín Rieta Sister, who was responsible for the restoration of the original state of the courtyard, whose ground floor arcs had been blinded before Rieta’s intervention. He opened these arcs by creating new wall gaps and installing regular windows there. This architect also removed some of the closed rooms on the ground floor, which were used for storage. Finally, he demolished the upper floor façade, turning the attic into a balcony using metallic handrails. After Rieta, architect Antonio Gómez Davó took charge of the work. He kept working on the courtyard, removing the last storage room left, and making three new gaps in the east façade, inspired by existing Neogothic doors. He demolished Rieta’s balconies and turned the upper floor into a useful space that met the requirements of the building to be used as a school. Gómez Davó increased the building’s height by turning this upper floor into a closed space and reconstructed the ashlar wall adding bilobed Gothic windows. From that moment, the courtyard was composed of a ground floor and two full upper floors. Both Rieta’s interventions, as well as the one carried out by Gómez, can be considered “in style”, as it was the ruling fashion at that moment to refurbish historic buildings, at least in Spain.